Endovascular treatment for the control of active vaginal bleeding from uterine cervical cancer treated with radiotherapy. (November 2018) - Chen, Cheng Shi; Park, Sohee; Shin, Ji Hoon; Nouri, Yasir; Kim, Jong-Woo; Yoon, Hyun-Ki; Ko, Gi-Young
Background: Endovascular treatment has become a significant therapeutic option for the management of intractable bleeding in gynecologic malignancies. However, the endovascular treatment types were almost never mentioned when active bleeding from different arteries was identified. Purpose: To present angiographic details and evaluate clinical efficacy of endovascular treatments to control active vaginal bleeding in uterine cervical cancer patients treated with radiotherapy. Material and Methods: In this retrospective study, six, consecutive cervical cancer patients treated with radiotherapy who underwent endovascular treatment for active vaginal bleeding were included. Angiographic findings, endovascular treatment details, and clinical outcomes were obtained. Results: Ten endovascular procedures were technically successful, in which bleeding arteries were the internal iliac artery/its branches (n = 5), external iliac artery (EIA) (n = 3), uterine artery (n = 1), and superior rectal artery (n = 1), and bleeding manifested as contrast extravasation (n = 6), pseudoaneurysm (n = 1), or both (n = 3). Three of the four repeated procedures showed different bleeding sites from the primary ones. Stent graft was inserted to preserve the patency of the bleeding EIA in two patients. For another EIA rupture, both proximal and distal embolization were performed, followed by femoral-to-femoral bypass to preserve blood flow. Bleeding control within one month was achieved in 80% (8/10). One minor complication, mild transient pelvic pain, occurred in one patient. Conclusions: Various endovascular treatment was feasible and effective to control active vaginal bleeding from cervical cancer. Repeated procedures showed commonly different bleeding foci and stent graft insertion was effective for preserving the patency of the large bleeding artery.